Changing Over From Criticism To Protectionism In Media Literacy Classes. Source Texts In Turkey - Sezgin, A. Asli (European Scientific Journal, ESJ, 2016)
Approachments, basically, are related to the subject of media literacy. The different practices sourced from these approachments have been remarked since the inception of media literacy subject discussions until today. The diversifying of media tools is dependent on its technological development. Thus, it is reaching broader areas which are necessary for evaluating the media literacy in a different and wider view. When the attempts of the government structures about the subject in Turkey and the courses were examined, wordings which have become different, over the years, in source texts have been given so much attention. Media literacy class source texts have been prepared in a critical language in Turkey. However, it is been passed into a protective and interferant wording in terms of time more than criticism. In this study, firstly, the differences between protective and interferant approachments will be explained with a critical approach directed towards media literacy. Right after that, the content of two (2) different sourced texts which has been prepared for study in the media literacy classes in Turkey will be examined based on the period they were published.